THE STRATEGY OF PREVENTING RADICALISM THROUGH REINFORCEMENT OF THE MOSQUE TA’MIR MANAGEMENT BASED ON ASWAJA ANNAHDLIYAH - Hamidulloh Ibda; Ziaul Khaq (Khazanah: Jurnal Studi Islam dan Humaniora, 2019)
This article’s aim is to discuss the strategies of radicalism preventing in mosques through strengthening Aswaja Annahdliyah’s Islamic-based of mosque takmir management that is tolerant, moderate, and upholds the Islamic principle of Rahmatan Lil-alamin. This field research uses descriptive qualitative method. Data collection was obtained from interviews and observations. The results of the study mentioned that from 104 mosques in Kandangan Subdistrict, Temanggung Regency, only 96 mosques had been noted  in the Nahdlatul Ulama Mosque Takmir Institute (LTM NU), while 8 other mosques had been not. After the research was carried out, four mosques were joined and had become members of the NU LTM and implemented the takmir management of the Aswaja Annahdliyah based mosque. There are seven strategies carried out, namely; (1) strengthening management of the ideals (management of the physical building of the mosque), imarah (management of  the activities of the mosque), and riayah (management of mosque hygiene), (2) forming LTM NU at the sub-district and village level, (3) forming  management of mosques takmir by involving all elements, (4) making syllabus/ curriculum for worship timetable, education and ritual activities, (5) giving tasks to takmir to maximize mosque functions, (6) strengthening administration  management and symbolizing mosques, (7) strengthening social economic empowerment in mosques. The strategy of strengthening the takmir of mosques management has been aligned with Talcott Parsons’ structural functionalism theory with schemes adaptation, goal attainment, integration, and latency (AGIL). There are challenges and opportunities that faced. In the internal aspects, namely limited access to the city center, low human resources, and lack of comprehensive knowledge about the management of takmir of mosque External aspects, namely the existence of four mosques still controlled by radical Islamic groups, and often there are religious studies in mosques from radical groups.